2015
DOI: 10.1186/s13287-015-0244-5
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated transfer of hepatocyte growth factor gene to human dental pulp stem cells under good manufacturing practice improves their potential for periodontal regeneration in swine

Abstract: IntroductionPeriodontitis is one of the most widespread infectious diseases in humans. We previously promoted significant periodontal tissue regeneration in swine models with the transplantation of autologous periodontal ligament stem cells (PDLSCs) and PDLSC sheet. We also promoted periodontal tissue regeneration in a rat model with a local injection of allogeneic bone marrow mesenchymal stem cells. The purpose of the present study is to investigate the roles of the hepatocyte growth factor (HGF) and human de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 31 publications
1
72
0
2
Order By: Relevance
“…DPSCs were isolated and cultured under good manufacturing practice (GMP) conditions as described in our previous studies [ 20 ]. Patients' teeth were acquired from Beijing Stomatological Hospital, Capital Medical University, and all treatments were performed per the approved guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…DPSCs were isolated and cultured under good manufacturing practice (GMP) conditions as described in our previous studies [ 20 ]. Patients' teeth were acquired from Beijing Stomatological Hospital, Capital Medical University, and all treatments were performed per the approved guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Research has also confirmed that Nrf2 itself influences the intrinsic and extrinsic apoptosis pathways at different levels [19]. Therefore, we believe that Nrf2 is extremely important in the process of cell apoptosis caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…To study the local bone formation using hDPSCs and SHED, cranial defects were created in rats on 11 manuscri-pts, 25 , 35 , 40 , 41 , 44 , 48 , 49 , 51 , 55 , 56 in mice on 4 manuscripts, 17 , 42 , 59 , 72 and in only one manuscript they were made on rabbits. 61 Furthermore, 10 studies created maxillary and mandibular bone defects 29 , 45 , 46 , 52 , 53 , 58 , 60 , 62 , 65 , 69 to assess the potential of hDPSCs for bone tissue engineering. In 3 out of these 10 studies, the researchers used the alveolar bone to test the tissue engineering strategies after extraction of third molars of maxillary 60 and mandibular 29 , 46 regions in humans.…”
Section: The Experimental Designsmentioning
confidence: 99%
“… 69 Six studies were conducted in different animal models. Among these studies, one used rats and created the bone defect in the anterior part of the maxilla, 58 one used rat and created the defect in the left side of mandible, 62 one used rabbits and created the defect between the first premolar and the mental foramen, 45 one used mini pigs to create the defects in the mesial region of the maxilla and mandibular first molars, 52 one used mini pigs and created the defect in front of the mandibular angle, 53 and one used dogs and created the defect on each side of the inferior mandibular border. 65 Furthermore, one study evaluated the potential of hDPSCs for bone tissue engineering in rabbits tibia submitted to distraction osteogenesis 68 and one study investigated the osteogenic potential of hDPSCs in an ovine model of induced osteonecrosis of femoral head.…”
Section: The Experimental Designsmentioning
confidence: 99%
See 1 more Smart Citation